Augment yourself through virtual mirror: the impact of self-viewing and narcissism on consumer responses. Issue 3 (4th May 2018) - Baek, Tae Hyun; Yoo, Chan Yun; Yoon, Sukki
Abstract : Virtual mirror, an increasingly popular application of augmented reality, allows consumers to view their visages overlaid with product images on digital displays. The authors of this study examine how augmented reality technology affects consumers' brand perceptions and purchase intentions. Study 1, using a real brand, demonstrates that consumers tend to form higher self-brand connections and purchase intention when viewing themselves trying a product via a virtual mirror, rather than when viewing professional models wearing the product. Study 2, using a fictitious brand, reveals that narcissistic participants show pronounced positive self-viewing effects, but non-narcissistic participants show attenuated effects. Implications for digital marketers are discussed.